The Effect of Voltaren and Brufen on The Heart - Marwa Bahri Mesbah; Dania Rajab Ahmed; Retaj Saleh Mohammed (Information Technology and Science (ITScience), 2024)
The study aimed to investigate the cardiovascular effects of two commonly used nonsteroidal anti-inflammatory drugs (NSAIDs), Voltaren (diclofenac) and Brufen (ibuprofen), on the heart. A total of 496 participants from Saudi Arabia were included in a cross-sectional descriptive study, utilizing an online questionnaire. The data revealed that both Voltaren and Brufen were associated with adverse cardiovascular effects, including pulse disturbance and hypertension. Specifically, chronic use of Voltaren and Brufen was linked to an increased risk of heart-related complications. The study emphasizes the need for heightened awareness among healthcare professionals and the general public regarding the potential cardiovascular risks associated with the use of these NSAIDs.